The Local Topological Reconfiguration in the Brain Network After Targeted Hub Dysfunction Attacks in Patients With Juvenile Myoclonic Epilepsy - Ke, Ming; Li, Huimin; Liu, Guangyao (Frontiers in Neuroscience, 2022)
Abstract: The central brain region of the brain network has been extensively studied in terms of various diseases. This study provides a direct measure of the brain's responses to targeted attacks on central regions, revealing the critical role of the central regions of the brain networks in patients with juvenile myoclonic epilepsy (JME). The resting-state data of 37 JME patients and 37 healthy subjects were collected, and brain functional networks were constructed for the two groups of data according to their Pearson correlation coefficients. The left middle cingulate gyrus was defined as the central brain region by the eigenvector centrality algorithm, and the central brain region was attacked by the CLM sequential failure model. The rich-club connection differences between the JME patients and healthy controls before and after the attacks were compared according to graph theory indices and the number of rich-club connections. We found that the numbers of rich connections in the brain networks of the healthy control group and the JME patient group were significantly reduced (p <0.05, false discovery rate (FDR) correction) before the CLM sequential failure attacks, and no significant differences were observed between the feeder connections and local connections. In the healthy control group, significant rich connection differences were obtained (p <0.01, FDR correction), and no statistically significant differences were observed regarding the feeder connections and local connections in the brain network before and after CLM failure attacks were conducted on the central brain region. No significant differences were obtained between the rich connections, feeder connections, and local connections in JME patients before and after CLM successive failure attacks on the central brain area. The rich connections, feeder connections, and local connections were not significantly different in the brain networks of the healthy control group and the JME patient group after CLM successive failure attacks on the central brain region. We concluded that the damage to the left middle cingulate gyrus is closely linked to various brain disorders, suggesting that this region is of great importance for understanding the pathophysiological basis of myoclonic seizures in JME patients.